Dari Ibadah ke Kebijakan Publik: Integrasi Zakat dalam Sistem Perpajakan di Indonesia - Ahmad Irfansyah Rosyadi; Salsabila Syifana Alkamila; Agita Naysilla Putri; Muhammad Lexsi Pratama; Ali Murtadho Emzaed (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Zakat and taxation are two important instruments in the life of society and the state, both of which aim to improve social welfare. However, in practice, the integration of zakat and taxation in Indonesia has not yet been fully realised, meaning that the potential of zakat as part of fiscal policy has not been optimally utilised. This study aims to examine the status of zakat within the legal system and public policy, the form of its integration into the tax system, and the various obstacles encountered in its implementation. This study employs a normative legal methodology using legislative, conceptual, and analytical approaches, and utilises secondary data analysed qualitatively. The research findings indicate that zakat has been recognised within the national legal system; however, it is still viewed as a religious obligation that coexists alongside taxation as a state obligation. The current integration remains limited to reductions in taxable income and has not yet demonstrated comprehensive coherence within fiscal policy. Furthermore, its implementation continues to face various obstacles from legal, institutional, technical, and fiscal perspectives, meaning it has not yet been effectively implemented.